Using N-terminal pro-B-type natriuretic peptide to diagnose cardiac abnormalities in children with dyspneaen with dyspnea - Zakaria Mukalla; Ria Nova; Legiran Legiran; Yangtjik Yangtjik (Paediatrica Indonesiana, 2017)
Background. Dyspnea could be caused by various reason, one of which is the presence of cardiac abnormality. Physical examination sometimes difficult to distinguish breath caused by heart abnormalities, especially small children, so we need another way to find out.Objective. To evaluate whether the examination of NT-proBNP levels can be used as a screening tool to diagnose cardiac abnormality in children presenting with dyspnea.Methods. A Cross sectional study was conducted from August to October 2015 on pediatric patients aged 1 month to 18 years presenting with dyspnea in pediatric ward Mohammad Hoesin Hospital Palembang. All subjects performed blood sampling for NT-proBNP examination and echocardiography to assess the presence of cardiac abnormalities. The diagnostic value analyzed by ROC curve, and determined the optimal cut-off point, sensitivity and specificity.Â Result. We obtained 58 subjects with median age 9.5 (1-180) months, consisted of 39 subjects with cardiac abnormalities and 19 subjects without cardiac abnormality. There is a significant difference (p = 0.002) of NT-proBNP levels in both groups with a medianÂ  1,775 (189-9,000) pg/ml vs 759 (245-9,000) pg/ml. In ROC curve analysis, AUC value was 0.75, and at the optimal cut-off point 1,235 pg/ml, sensitivity was 74.4% and specificity was 73.7%.Conclusion. The level of NT-proBNP can be used to diagnose cardiac abnormalities in children presenting with dyspnea.